A Brazilian Perspective on Quality and Sustainability Aspects of Open Educational Resources in Computing Education - Carvalho, Ágata Meireles; Silva, Williamson; Oliveira, Alessandreia Marta de; Valle, Pedro Henrique Dias (Anais do Simpósio Brasileiro de Educação em Computação (EDUCOMP); 2026: Anais do VI Simpósio Brasileiro de Educação em ComputaçãoDO - 10.5753/educomp.2026.18662, 2026)
Universities are increasingly adopting new technologies to enhance teaching, with Open Educational Resources (OER) playing a central role in expanding access to high-quality learning materials. However, although many OER are produced, these resources are underutilized, become outdated, or lack design elements that ensure long-term sustainability. This work identifies essential characteristics that support the effective and lasting integration of OER into educational practice. We conducted a survey and semi-structured interviews with Computing instructors who develop or use OER. The findings highlight key attributes that support OER reuse, maintenance, and longevity, underscoring the need for further research to inform sustainable OER design and development.